Context of Scientific and Institutional Renewal in Islamic Higher Education (PTKI): A Study on Azyumardi Azra’s Thought 1998-2015 - .M, Iswantir (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2018)
Azyumardi Azra’s Thought 1998-2015. The practice of modernization of Islamic education has been demonstrated by Azyumardi Azra at State Islamic University (UIN) of Jakarta. The type of the research used is the study of thinking figures, which is called a research figure or an individual life history. This type of the research is classified as qualitative research. The focus of this research is to identify Azra’s thoughts in the context of intellectual thinking and institutional perspective in renewing Islamic thoughts in Indonesia. This study uses primary and secondary data sources. The primary data source is a character that became the object of research, because the character is still alive, and then the primary data source in this study is Azyumardi Azra and his work. The other complement data is taken from books, papers, and journals. The result of the research indicated that the context of intellectual thinking and institutional perspectives of Azra in the renewal of Islamic thoughts in Indonesia has the same mission, namely to eliminate the scientific dichotomy in the development of PTKI. A scientific development with integrative paradigm requires an institutional transformation of State Islamic Collage (STAIN) or State Institute for Islamic Studies (IAIN) into State Islamic Universiy (UIN).